Pengaruh Pembiayaan Mudharabah dan Pembiayaan Musyarakah terhadap Non Performing Financing pada Bank Syariah Periode 2015-2022 - Nabila Qolbi Nur Insani; Kania Nurchoisah; Irena Paramita Pramono (UNISBA Press, 2024)
Abstract. Financing channeled by Islamic Banks is very likely to contain risks in it, one of which is problematic financing which has a high risk if the money borrowed is not returned. Financing risk can be seen from the level of Non Performing Financing (NPF) which consists of substandard, doubtful and non-performing financing with total financing disbursed as a whole. Profit sharing financing is perceived by Islamic Bank management as high risk financing. This study aims to examine the effect of Mudharabah Financing and Musyarakah Financing on Non Performing Financing. In this research the method used is descriptive method with quantitative approach. The sampling technique used purposive sampling so that the sample obtained in this study was 6 Islamic Commercial Banks registered with the Financial Services Authority (OJK) for the period 2015-2022, so that 48 observations were obtained. The data collection technique used in this study is using financial reports. Based on the results of the F test, it shows that Mudharabah Financing and Musyarakah Financing have an effect on Non Performing Financing at Islamic Commercial Banks registered with the OJK for the 2015-2022 period. Based on the results of the t test, it shows that Mudharabah Financing has an effect on Non-Performing Financing and Musyarakah Financing has an effect on Non-Performing Financing at Islamic Commercial Banks registered with the OJK for the 2015-2022 period. Abstrak. Pembiayaan yang disalurkan oleh Bank Syariah sangat mungkin mengandung resiko di dalamnya, salah satunya pembiayaan bermasalah yang memiliki resiko tinggi jika uang yang dipinjam tidak kembali. Resiko pembiayaan dapat dilihat dari tingkat Non Performing Financing (NPF) yang terdiri dari pembiayaan kurang lancar, diragukan dan macet dengan total pembiayaan yang disalurkan secara kesuluruhan. Pembiayaan bagi hasil dipersepsikan oleh manajemen Bank Syariah sebagai pembiayaan high risk. Penelitian ini bertujuan untuk menguji pengaruh Pembiayaan Mudharabah dan Pembiayaan Musyarakah terhadap Non Performing Financing. Dalam penelitian ini metode yang digunakan adalah metode deskriptif dengan pendekatan kuantitatif. Teknik pengambilan sampel menggunakan purposive sampling sehingga sampel yang didapat dalam penelitian ini adalah 6 Bank Umum Syariah yang terdaftar di Otoritas Jasa Keuangan (OJK) periode 2015-2022, sehingga diperoleh pengamatan sejumlah 48. Teknik pengumpulan data yang digunakan dalam penelitian ini yaitu menggunakan laporan keuangan. Berdasarkan hasil uji F, menunjukkan bahwa Pembiayaan Mudharabah dan Pembiayaan Musyarakah berpengaruh terhadap Non Performing Financing pada Bank Umum Syariah yang terdaftar di OJK periode 2015-2022. Berdasarkan hasil uji t, menunjukkan bahwa Pembiayaan Mudharabah berpengaruh terhadap Non Performing Financing dan Pembiayaan Musyarakah berpengaruh terhadap Non Performing Financing pada Bank Umum Syariah yang terdaftar di OJK periode 2015-2022.